1995
DOI: 10.1002/ajhb.1310070210
|View full text |Cite
|
Sign up to set email alerts
|

Racial admixture in a Mestizo population from Mexico City

Abstract: Seven genetic systems were used to investigate the racial composition of a sample from a low-income Mexico City Mestizo group, finding estimates of 0.590, 0.348, and 0.062 of Indian, White, and Black ancestry, respectively. The results are similar to another Mexico City group studied previously and to several Mestizo populations from different parts of the country. The one thing in common in all these groups is low socioeconomic status. There is only one report suggesting that Mexico City Mestizos have around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 10 publications
0
24
2
Order By: Relevance
“…Native American ancestry, on the other hand, ranges from 31% in Veracruz to 76% in Tlaxcala (Crawford et al, 1974). In addition, all Mexican Indian groups exhibit some degree of admixture, mainly with Europeans, starting from $9% in the Huichol up to $37% in the Huasteco (Lisker et al, 1996). Thus it appears that Mestizo groups in Mexico, especially those from lower socioeconomic strata, differ from Mexican Indian populations more culturally than genetically (Lisker et al, 1996).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Native American ancestry, on the other hand, ranges from 31% in Veracruz to 76% in Tlaxcala (Crawford et al, 1974). In addition, all Mexican Indian groups exhibit some degree of admixture, mainly with Europeans, starting from $9% in the Huichol up to $37% in the Huasteco (Lisker et al, 1996). Thus it appears that Mestizo groups in Mexico, especially those from lower socioeconomic strata, differ from Mexican Indian populations more culturally than genetically (Lisker et al, 1996).…”
mentioning
confidence: 89%
“…Estimates of admixture in Mexican Indian populations show levels of European admixture ranging from 8.8% in the Huichol to 37.3% in the Huasteco, as determined by the analysis of blood groups and serum proteins (Lisker et al, 1996). The European ancestry estimate for a Nahua population obtained by Lisker et al (1996) was 29.6%.…”
Section: Population Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Binding sites for transcription related 21) and their genome has undergone fewer recombination events than Mexicans. Genetic studies of Mexicans have shown that the proportion of Indian and White genes is 56% and 44%, respectively, in the dihybrid model and 3%, 56% and 41% from Blacks, Indian and White in the trihybrid model [22][23][24] . Genetic heterogeneity is a well-recognized reason for the failure to replicate genetic association findings.…”
Section: Discussionmentioning
confidence: 99%